2023
DOI: 10.3389/fendo.2023.1202044
|View full text |Cite
|
Sign up to set email alerts
|

Programmed frozen embryo transfer cycles are associated with a higher risk of abnormal placental development: a retrospective cohort study of singleton live births

Abstract: IntroductionAbnormal placental development can lead to adverse outcomes for both mother and fetus. The effect of different types of endometrium preparation regimens of frozen-thawed cycles on the placental development features associated with the perinatal outcomes remains unclear. Hence, we conducted a retrospective cohort study to assess the impact of specific endometrial preparation regimens on placenta-mediated pregnancy complications in singleton live births.MethodsA retrospective cohort study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Vasoactive products, such as relaxin and vascular endothelial growth factor, produced by the corpus luteum have protective effects on the maternal cardiovascular system. In addition, some studies have shown that the incidence of adverse pregnancy outcomes, such as ectopic pregnancy and placental abnormalities, are significantly greater in the HRT group than in the NC group [ 19 , 20 ]. The NC regimen seems to be superior to the HRT regimen in terms of safety, but it is not necessarily the first choice of clinicians in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Vasoactive products, such as relaxin and vascular endothelial growth factor, produced by the corpus luteum have protective effects on the maternal cardiovascular system. In addition, some studies have shown that the incidence of adverse pregnancy outcomes, such as ectopic pregnancy and placental abnormalities, are significantly greater in the HRT group than in the NC group [ 19 , 20 ]. The NC regimen seems to be superior to the HRT regimen in terms of safety, but it is not necessarily the first choice of clinicians in practice.…”
Section: Discussionmentioning
confidence: 99%